Robust closed-loop supply chain model with return management system for circular economy - Shin, Youngchul; Kim, Gwang; Jeong, Yoonjea (Computers and Industrial Engineering, 2025)
The significance of the circular economy (CE) is increasingly recognized worldwide due to its substantial global environmental impacts. To address this critical issue from a supply chain management perspective, we propose an optimization model for a closed-loop supply chain that integrates CE operations, including reuse, remanufacturing, and recycling processes. To capture correlations between uncertain end-customer demand and three types of return processes, we adopt a factor-based demand model. Since these types of uncertain correlated parameters make the optimization problem intractable, we utilize a linear decision rule and a distributionally robust bound to retain computational tractability from a deterministic formulation. Consequently, we derive a deterministic second-order cone program, which is solvable using an interior point method within reasonable times for moderate-size data. The computational results show that the proposed model achieves significant cost savings effects, contributing positively to the CE operations.
Keywords: Circular economy; Closed-loop; Closed-loop supply chain; Deterministics; Global environmental impacts; Management systems; Returns managements; Reverse logistics; Robust optimization; Supply chain modeling; Circular economy; Closed-loop supply chain; Reverse logistics; Robust optimization